The Influence of Korean Drama Series on Behavioral Changes Among Adolescents - Azahra, Savira Nurhaliza; Marlina, Yuli (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study addresses the growing consumption of Korean Drama among students at the Islamic University of Jakarta and its suspected impact on adolescent behaviour spanning lifestyle, social interaction, and religious practice. The research aims to quantify the influence of Korean Drama exposure on behavioural change and to clarify its implications for character development on campus. A quantitative correlational survey was employed, using purposive sampling to draw 33 respondents from a population of 133 fourth and sixth semester students. Data were gathered through a validated closed?ended questionnaire and analysed with the product moment correlation test. Findings reveal a correlation coefficient of r=0.593 (p<0.01) and an adjusted R² of approximately 0.60, indicating a moderate yet significant relationship between viewing intensity and behavioural change. These results suggest that Korean Drama can foster positive outcomes such as motivation to learn foreign languages while simultaneously posing risks, including heightened consumerism and diminished religious discipline. Consequently, the study recommends campus based media literacy initiatives and psychosocial mentoring to maximize the benefits of Korean Drama and mitigate its adverse effects through strengthened selfcontrol and reinforcement of Islamic values.